Volume 2: Structures, Safety and Reliability 2011
DOI: 10.1115/omae2011-49507
|View full text |Cite
|
Sign up to set email alerts
|

Wave Slam/Slap Loads on Structural Members in the Air-Gap

Abstract: The offshore platforms shall be designed with deck elevation that maintains sufficient air-gap with maximum predicted wave crest elevations. However, due to compelling reasons of hydrocarbon process and changes to water levels/seabed subsidence may have structures in the close vicinity of the sea level or submerged. Hence the assessment of wave induced forces on the deck structures especially the old platforms become very essential. Review of literature indicates that the previous studies focused mainly on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was recommended that dynamic amplification factor (DAF) shall not be applied for wavein-deck loads. Sekhar and Nallayarasu (2011) investigated the wave slam and slap load on non-circular shapes present in deck structures of offshore platforms. It was reported that the slap coefficient (C P ) decreases as the wave period (T) increases and the slam coefficient (C S ) increases as the wave period (T) increases in most of the test cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was recommended that dynamic amplification factor (DAF) shall not be applied for wavein-deck loads. Sekhar and Nallayarasu (2011) investigated the wave slam and slap load on non-circular shapes present in deck structures of offshore platforms. It was reported that the slap coefficient (C P ) decreases as the wave period (T) increases and the slam coefficient (C S ) increases as the wave period (T) increases in most of the test cases.…”
Section: Literature Reviewmentioning
confidence: 99%